Mediating Effect Of Stress Response and Grit On the Relationship Between Stress and Depression In Nursing Students: Emperical Research Quantitative - Jaehee Jeon; Seunghye Choi (Wiley, 2024)
ABSTRACT Aims To explore the prevalence of depression amongst Korean nursing students and to identify the mediating effect of stress response and grit in the relationship between stress and depression in the same population. Design A total of 184 nursing students from Korea were included. This study was cross‐sectional with a structured questionnaire that included stress, stress response, grit, and depression. Methods The study participants were university students from four nursing colleges located in the metropolitan area and Gangwon‐do in South Korea. The data collection period spanned from February 24 to March 30, 2023, using an online questionnaire following the G University's Institutional Review Board's (IRB's) deliberation. Results Amongst the participants, the prevalence of depression was 23.8% (95% CI: [17.7%, 29.9%]), and 13.7% had moderate depression, whereas 10.1% had severe depression. The direct effects of stress on stress response (t = 9.26, p < 0.001) and from stress to grit (t = 22.82, p < 0.001) were statistically significant. The direct effects from stress to depression (t = 2.61, p = 0.009), from stress response to depression (t = 9.68, p < 0.001), and from grit to depression (t = −2.09, p = 0.039) were also statistically significant. The association between stress and depression was mediated by stress response but not grit. Conclusions The prevalence of depression amongst Korean nursing students was high. Preparing strategies against depression amongst nursing students is an urgent matter. The mediating effect of stress response in the relationship between stress and depression was statistically significant, but that for grit was not. Therefore, it is necessary to investigate students' stress responses and provide personalised interventions, as well as reduce established stressors. Implications for the Profession Strategies to manage stress responses can be used to reduce depression caused by stress in nursing students. Impact To reduce depression in nursing students, it is necessary to investigate strategies to understand stress response, provide personalised interventions, and reduce already‐known stressors. Reporting Method The authors have adhered to relevant EQUATOR guidelines using the STROBE checklist: cross‐sectional studies. Patient or Public Contribution Nursing students were the subjects of data collection for this study and participated in the survey upon voluntary consent to participation.